Influence of Predisposing Factors, Encouraging Factors and Supporting Factors on Medical Record Recording at Mitra Medika Hospital Medan in 2022 - Sari, Nila; Siahaan, Agnes Amabel (Sean Institute, 2022)
Law of the Republic of Indonesia Number: 29 of 2004 concerning Medical Practice, which includes the obligation of doctors and dentists to make medical records. The results of the evaluation of the completeness of medical records at Mitra Medika General Hospital Medan were still found to be incomplete medical record files. This study aims to determine the influence of predisposing factors (knowledge), driving factors (encouraging from other officers) and supporting factors (facilities and facilities) on the behavior of doctors in recording medical records. The data obtained were analyzed with several statistical tests using a computer program, namely using univariate analysis, namely to see the description and characteristics of each independent variable (free) and bivariate analysis, namely to test and analyze each effect with the completeness of recording medical records at RSU Mitra Medika Medan using the Chi- Square test. The results of this study indicate that the completeness of medical record recording was obtained from 27 people with a good number of 18 people (66.7%), good completeness of complete medical record recording as many as 10 people (37.0%) and good completeness of medical record recording not complete as many as 8 people (29.7%), while the encouragement of other personnel for recording medical records was obtained from 27 people with the number of other staff encouragement both as many as 20 people (74.1%), then other facilities and facilities for recording medical records were obtained from 27 people with good facilities and facilities as many as 22 people (81.4%). Based on the results of this study, it can be concluded that there is an effect of completeness on the recording of medical records at Mitra Medika Hospital in Medan. The results of statistical tests using the chi- square test showed that the p-value was 0.006 <0.05. The results of the statistical tests using the chi-square test showed that the p-value was 0.978 > 0.05.